Enhancing the solubility of crystalline nanocellulose (cnc) via dissolution of coconut husk - Lai, Min Yan (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
The crystalline nanocellulose (CNC) is one subcategory of nanocellulose. The demand of nanocellulose has to increase tremendously over last few decades due to numerous applications in industry and bio-based product. In this project, CNC has been produced by dissolution of coconut husk using acid hydrolysis. Alkaline pre-treatment has been carried out to remove lignin and hemicellulose. The modeling of the design of experiment for optimization study of the dissolution process is conducted by using Design Expert software version 7.1.6. This experimental design is conducted in order to optimize the solubility of CNC with a significant parameter that affecting the solubility of CNC. The parameters that have been used are reaction time, solid to liquid ratio and acid concentration. The design of experiment (DOE) software has been carried out; the optimum condition to obtain highest CNC solubility was at 120 min, 60 % acid concentration and 1:25 g/mL solid to liquid ratio with the 32.022 % CNC solubility. CNC produced has been analysis using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). This research will focus on the preparation of CNC and its optimization condition to enhance the solubility of CNC from coconut husk.